Single-cell profiling reveals IFI44L as a central regulator of immune dysregulation in high HIV viral load - Jiamin Gao; Yanjun Li; Jinping Huang; Xianzhen Huang; Qingdong Zhu; Cailing Wei; Jieling Chen; Shunda Luo; Zhouhua Xie (Medical Microbiology and Immunology, 2026)

Enhancing soil ecosystem multifunctionality via carbon input and enzymatic catalysis in cover crops under antibiotic contamination - Ju Wang; Huanhuan Zhang; Jintao Yu; Xuechen Zhang; Mingjun Li; Peizhi Yang; Ziyan Li (Applied Soil Ecology, 2026)

Diorcinol L, a natural pentenyl diphenyl ether isolated from Aspergillus sp. MA6037, exhibits cytotoxic activity by inhibiting KIF11 - Yujun Liu; Chao Tang; Heyi Zhang; Lingying Kong; Hua Sui; Yuzhuo Wu (Archives of Microbiology, 2026)

Fractionation due to soil–water interactions affects global isotopic evapotranspiration partitioning - Shaojie Hu; Chao Zhang; Lijun Li; Dani Or; Ning Lu; Renpeng Chen (Advances in Water Resources, 2026)

Depth heterogeneity within surface soils substantially affects microbial abundance, diversity, and co-occurrence patterns - Guanyu Chai; Yuan Du; Zelin Wang; Kaifang Liu; Yuan Chi; Yi Duan; Shuo Ma; Xin Hu; Rongxiao Che; Jianxing Li; Wenjun Liu; Dong Liu (Journal of Soils and Sediments, 2026)

Predictive, preventive, and personalized medicine in statin-treated patients with NSTE-ACS, HFpEF, and type 2 diabetes: a data-driven model for long-term residual risk assessment - Zeyan Li; Hengyang Liu; Li Xu; Wenyuan Yin; Jiajun Zhu; Bowen Zhou; Bing Wu; Tongjian Zhu; Hui Li; Jinjun Liu; Yijun Wang; Jun Wang (EPMA Journal, 2026)

Annual Variation of Secondary Organic Aerosols from Isoprene, α/β-Pinene, β-Caryophyllene, and Aromatics in Tropical Rainforest Area of Southwest China - Xiao Guo; Yali Liu; Minxia Shen; Weining Qi; Yifan Zhang; Lu Li; Yue Cao; Yingkun Jiang; Qian Wang; Shicong Li; Zhuoer Dong; Wenting Dai; et al. (Aerosol Science and Engineering, 2026)

Synergic anticancer effects of morin hydrate and sorafenib delivered via polymeric iron oxide nanoparticles for the treatment of triple-negative breast cancer - Mingjun Li; Chaohui Wang; Zhenhua Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Heterogeneous Response and Zonal Micromechanical Deterioration of Deep Rock-forming Minerals Under Laser Irradiation - Yuanru Li; Mingzhong Gao; Xuemin Zhou; Yanbo Bai; Junjun Liu; Lei Yang; Haichun Hao; Bengao Yang; Jing Xie; Zheng Gao (Rock Mechanics and Rock Engineering, 2026)

Correction: Cullin 3 overexpression inhibits lung cancer metastasis and is associated with survival of lung adenocarcinoma - Jiayu Zhou; Shizhen Zhang; Yong Xu; Weiwen Ye; Zhijun Li; Zhoumiao Chen; He Zhengfu (Clinical & Experimental Metastasis, 2026)

Plant growth stage drives the differentiation of microbial assemblage across plant niches - Li Shao; Jiajun Li; Ting Lu; Tangfu Xiao; Aiwen Wu; Xiuping Li; Jinmei Deng; Enzong Xiao (Applied Soil Ecology, 2026)

Identification and complete genome sequence of a novel secovirus infecting Broussonetia kaempferi in China - Jinhong Yang; Jun Ling; Wei Jiang; Weiqing Kong (Archives of Virology, 2026)

Multi-phase PAH transport across the land-sea continuum: Mechanistic drivers of source-sink dynamics and socioeconomic modulation - Yang Ye; Huijun Liu; Jiajie Hu; Minggang Cai; Lixiao Chen; Mengyang Liu; Zhiheng Li; Zhiguo Fang; Wenlu Zhao (Marine Pollution Bulletin, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

Intergeneric hybridization of Chanodichthys erythropterus (♀) and Culter alburnus (♂) generates fertile diploid hybrids - Xu Huang; Xiaoyu Huang; Jian Li; Jiaxuan Zhu; Jiawang Huang; Can Xu; Lang Qin; Yingying Yang; Hongxuan Liang; Yuxiang Wang; Fangzhou Hu; Chang Wu; et al. (Aquaculture, 2026)

Decoupling predictors of arbuscular mycorrhizal fungal α- and β-diversity: Plant phylogeny versus functional traits in an alpine artificial grassland of Three-River Source Region - Guoxi Shi; Yingli Ma; Ning Wu; Meiling Guo; Xinchuang Wang; Yongjun Liu; Huyuan Feng; Huakun Zhou; Buqing Yao (Applied Soil Ecology, 2026)

Influences and underlying mechanisms of substituting chemical nitrogen fertilizer with different organic amendments on soil nitrogen mineralization in red soil - Jiajun Lin; Yun Chen; Jiajun Lai; Jiying Peng; Xiaolong Wang (Applied Soil Ecology, 2026)

Microbial interaction strategies of active bacteria shape carbon priming in intensively managed citrus orchard soils - Man Hu; Yunlong Cai; Zonglin Shi; Tianrui Zhai; Hui Zhang; Lianhao Zhou; Jun Li; Quan Zhou; Quanchao Zeng (Applied Soil Ecology, 2026)

Organic fertilization improves activities of phosphomonoesters hydrolase in rhizosphere to facilitate phosphorus acquisition in cucumber and accumulates organic phosphorus in soil - Bingshuang Wang; Yuan Wang; Xihe Zhang; Xiaodan Hu; Shujun Li; Yifei Sun; Yang Wang; Yan Sun; Ziwei Dai; Yunsheng Lou; Rong Li; Guohua Xu; et al. (Applied Soil Ecology, 2026)

Distribution and health risk assessment of heavy metals in the soil and tea of the Yangai tea farm - Yun Huang; Haijie Song; Rou Wang; Jing Shi; Jianhong Liu; Yishu Peng; Tao Jin; Jianjun Liu (Applied Soil Ecology, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Fungicide, not nitrogen, reduces soil nematode diversity and multifunctionality in alpine grasslands - Yali Zhang; Hao Xi; Joann K. Whalen; Jiayao Han; Xiang Liu; Yongjun Liu (Applied Soil Ecology, 2025)

Microbial network stability in chlorpyrifos-contaminated soils is improved by microbial inoculant application - Chunxiao Wu; Zefang Tong; Meihuan Lu; Lijun Li; Yalei Pan; Yinghui Ma (Applied Soil Ecology, 2025)

Impact of plant litter decomposition on soil microbial diversity and ecosystem multifunctionality - Quanchao Zeng; Lianhao Zhou; Quan Zhou; Jun Li; Zhe Chen; Man Hu; Wenfeng Tan (Applied Soil Ecology, 2025)

Straw return combined with water-saving irrigation improves soil quality and rice yield by regulating microbial community structure in paddy fields - Tangzhe Nie; Haijun Liu; Peng Chen; Lili Jiang; Tianyi Wang; Tiecheng Li; Kechun Wang; Zhongxue Zhang (Applied Soil Ecology, 2025)

Vegetation restoration promotes glomalin-related soil protein accumulation via mineral interactions in a Karst Region, southwest China - Xiao Lan; Zihong Zhu; Xinyu Hou; Kongcao Xiao; Zhongcheng Wang; Dejun Li (Applied Soil Ecology, 2025)

Long-term plastic film mulching promotes microplastic accumulation and alters gross nitrogen transformation in soil - Jinrui Zhang; Kai Wang; Tianxiang Hao; Jinbo Zhang; Christoph Müller; Perrine Florent; Hong Yan; Siyang Ren; Kaijing Qu; Kaige Ren; Jingjing Li; Yiting Su; et al. (Applied Soil Ecology, 2025)

Mixed vineyard prunings and sheep manure compost: Creating changes in vineyard soil dominant microbiota to impact fruit quality - Qian Tu; Yuanyuan Li; Weikang Ding; Shubo Zhou; Yanping Huang; Shiqiu Liu; Xuwu Min; Jiarui Zhang; Junjun Li; Chunlong Yuan (Applied Soil Ecology, 2025)

Long-term effects of nitrogen fertilization and Bradyrhizobium inoculation on diazotrophic community structure and diversity in soybean cultivation - Wanling Wei; Mingchao Ma; Xin Jiang; Fenliang Fan; Fangang Meng; Fengming Cao; Huijun Chen; Dawei Guan; Li Li; Jun Li (Applied Soil Ecology, 2025)

Changes in soil microbial community and carbon use efficiency in freeze-thaw period restored after growth season under warming and straw return - Minghui Liu; Zhiming Zhang; Peng He; Yifei Zhang; Lu-Jun Li (Applied Soil Ecology, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

Corrigendum to “Characteristics of microbial community during the different growth stages of yam (Dioscorea opposita Thunb. cv. Tiegun)” [Appl. Soil Ecol. 201 (2024) 105519] - Zhao Qin; Weichao Zhao; Haitao Ma; Jin Gao; Ruifei Wang; Chaochuang Li; Hao Zhang; Mingjun Li; Qingxiang Yang (Applied Soil Ecology, 2024)

Drivers of denitrification and nitrification in a dryland agroecosystem: The role of abiotic and biotic factors - Zhou Fang; Zhenling Peng; Yali Zhang; Jiayao Han; Jianbin Pan; Qi Zhang; Lin Mao; Guoxi Shi; Yongjun Liu; Huyuan Feng; Xavier Le Roux (Applied Soil Ecology, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Carbon exchange of forest plantations: global patterns and biophysical drivers - Xiaojuan Tong; Jingfeng Xiao; Peirong Liu; Jinsong Zhang; Jingru Zhang; Peiyang Yu; Ping Meng; Jun Li (Agricultural and Forest Meteorology, 2023)

Boundary-to-solution mapping for groundwater flows in a Toth basin - Jingwei Sun; Jun Li; Yonghong Hao; Cuiting Qi; Chunmei Ma; Huazhi Sun; Negash Begashaw; Gurcan Comert; Yi Sun; Qi Wang (Advances in Water Resources, 2023)